Implementation of Nurse-Doctor Interprofessional Collaboration During the COVID-19 Pandemic According to Nurses' Perceptions in Hospital - Naela Farah Anisa; Anisah Ardiana; Dicky Endrian Kurniawan; Nurfika Asmaningrum; Alfid Tri Afandi (Jurnal Kesehatan Pasak Bumi Kalimantan, 2023)
The COVID-19 pandemic poses significant challenges to the collaborative process between health workers. In handling a pandemic, every health professional must collaborate and coordinate with other professionals to produce safe and quality health services. Interprofessional collaboration is a general strategy to achieve the desired quality results effectively and efficiently in improving health services. This study aims to determine the implementation of nurse-doctor collaboration in inpatient rooms based on the perspective of inpatient nurses. This study used a descriptive research approach through a total sampling technique and as many as 151 inpatient nurses at dr. Soebandi Hospital participated as a respondent. Data was collected using a nurse characteristic questionnaire and NPCS (Nurse-Physician Collaboration Scale). Data were analyzed using descriptive methods and categorized as good and bad collaboration. The results showed that 51.7% of nurses had good interprofessional collaboration, and 48.3% reported bad interprofessional collaboration. The results showed that interprofessional collaboration between nurses and doctors showed almost the same results; nearly half of the nurses' perceptions showed results that still needed to be improved. There is a need to increase interprofessional collaboration in all hospital services. Even though the pandemic is a limitation for direct collaboration, collaboration is further enhanced by using supporting communication media, such as by telephone. Good collaboration between doctors and nurses will improve the quality of health services.